Providing chest physiotherapy and pursed lip breathing to childern with acute respiratory tract infections - putri, Rizky Amalia Prima (Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Background: Acute respiratory infections are upper and lower respiratory tract infections caused by various pathogens. Chest physiotherapy is an attempt to clear the airways and excess secretions. Pursed lip breathing helps control breathing with extended exhalation time.Objective: To analyze the differences between chest physiotherapy and pursed lip breathing on increased peak exhalation flow, oxygen saturation, and decreased degrees of shortness of breath.Methods: The type of research is qualitative, pre- and post-experimental research methods with static group comparison design using purposive sampling techniques. There were 48 respondents divided into two groups. Group I ARI patients were given chest physiotherapy, and Group II ARI patients were given pursed lip breathing, which was done in six weeks.Results: Paired Sample T Test (p=0,000) and Independent Sample T Test (p=0.027) Peak Expiration Flow, (p=0.049) Respiratory Rate, and (p=0.040) oxygen saturation. Results of study: There were significant differences between chest physiotherapy and pursed lip breathing regarding increased peak exhalation flow, oxygen saturation, and decreased degrees of breathing.Conclusion: Chest physiotherapy is quicker to help cleanse the airway and reduce complaints than pursed lip breathing, which the patient himself practices.